Study on mechanism of action of β-elemene in inhibiting cisplatin resistance in lung cancer through LncRNA LINC00511 - Deng, Xiaoli; Hu, Chunjie; Li, Lin; Yang, Guixian; Li, Chikun; Zhang, Wanxun; Cheng, Guangyu (Frontiers in Pharmacology, 2025)
BackgroundLung cancer is a leading cause of cancer-related deaths, with cisplatin being a cornerstone of treatment. However, resistance to cisplatin presents a significant challenge. β-elemene, a natural compound, has demonstrated potential to reverse cisplatin resistance. LncRNA LINC00511 has been implicated in cisplatin resistance through its role in activating the PI3K/AKT/mTOR pathway, which supports tumor survival and proliferation.PurposeThis study aims to investigate the mechanism by which β-elemene overcomes cisplatin resistance in lung cancer by regulating LINC00511.MethodsHuman lung adenocarcinoma cells (A549 and A549/DDP) were treated with β-elemene and cisplatin. Cell proliferation and apoptosis were assessed using CCK-8, EdU staining, and flow cytometry. LINC00511 expression was measured by qRT-PCR, and protein levels of PI3K, AKT, and mTOR were evaluated via Western blot. A xenograft model was used to confirm in vivo effects.Resultsβ-elemene significantly enhanced cisplatin-induced apoptosis in A549/DDP cells, reduced LINC00511 expression, and inhibited the PI3K/AKT/mTOR pathway. LINC00511 knockdown further potentiated these effects, both in vitro and in vivo. Xenograft models confirmed the enhanced anti-tumor effects of the combination treatment.Conclusionβ-elemene overcomes cisplatin resistance in lung cancer by downregulating LINC00511 and inhibiting the PI3K/AKT/mTOR pathway. These findings propose a promising therapeutic strategy for treating cisplatin-resistant lung cancer.